The relationship between ownership structure and bank performance: A Malaysian case - Norizan, Samri (2013)
This study analyzes the relationship between ownership structure and bank performance in Malaysia. The empirical analysis of this study is restricted to Malaysian Commercial Banks during the period of 2001-2011. The main objective of this study is to examine the relationship between ownership structure and performance in commercial bank in Malaysia. The results show that different types of ownership have different impact on bank performance. The result also shows that foreign ownership had largest impact to bank performance compared to other types of ownership structure. Higher shares by institutional tend to induce larger monitoring which leads to better performance of the banks. However, the results indicate that higher insider ownership and family ownership would increase agency problem in the banks. Government ownership is found to have no impact on the banks performance